Desafios no atendimento a mulheres vítimas de violência de gênero na universidade - Carvalho, Natalia (Universidade Federal de São Carlos, 2023)
Gender violence is a public health problem that mostly affects women, harming their mental and physical health. This type of violence also finds space in the university field, causing the women involved to have their academic and professional performance affected. To combat this phenomenon, it is necessary to act together, involving different sectors, such as health, education, social assistance, public security, culture, justice, among others. Furthermore, it is necessary to qualify professionals who mobilize new knowledge that contribute to care with potential for the emancipation of women. The present study sought to investigate the performance of administrative technicians from a federal university with victims of gender violence, identifying the challenges and difficulties experienced by these professionals. Eight administrative technicians participated in the research, 5 females and 3 males, aged between 32 and 61 years (M= 39.37; SD= 9.95), most with postgraduate degrees. (87.5%) and all carried out activities to assist university students. The results showed that the participants have knowledge about gender violence, efficient tools and techniques to promote a comprehensive care model and knowledge of the care network. Difficulties related to structural issues were evidenced, such as the lack of policies and measures to confront, disarticulation and sectorialization of actions and victimization of the victim. Possibilities for preventing and coping with gender violence at the university are discussed, in order to think of actions that contribute to an egalitarian academic environment and, consequently, conducive to the academic and professional development of women.
Challenges in care of women victims of gender violence at the university
Keywords: Violência de gênero; Universidade; Enfrentamento; Gender violence; University; Confrontation; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA